CLINICAL AND LABORATORY ASPECTS OF VIRAL INFECTIONS (Modern education and development, 2025)
Definition - anthroponotic viral acute infectious disease with fecal-oral transmission mechanism. Characterized by predominant lesions of the digestive tract, general intoxication, dehydration. Food poisoning The causative agent is an RNA-containing virus from the family Reoviridae of the genus Rotavirus. The name is derived from the Latin rota - wheel, as the virus particles under the electron microscope look like small wheels with a wide “hub”, 20 short “spokes” and a circular rim. Contains hemagglutinins.